Sustained growth in primary culture of normal mammary epithelial cells embedded in collagen gels - Yang, Jason (1980)
Normal mammary epithelial cells from BALB/cfC3H midpregnant mice were freed from stromal cell types by Percoll density gradient centrifugation after collagenase digestion and were then embedded within collagen gels. Sustained growth leading to an increase in cell number was accomplished in response to cholera toxin and high concentrations of horse serum. The extent of growth was found to be dependent on the horse serum concentration, the maximum growth being attained at 50%. A serum concentration of 12.5% horse serum and 2.5% fetal calf serum, along with cholera toxin at 0.01 μg/ml, allowed maintenance but failed to cause any significant increase in cell number during the experimental period of 2 weeks. This same maintenance medium was used to determine the effects of various exogenously added steroids, protein hormones, and organ extracts on the proliferation of mammary epithelial cells in culture. Hormones failed to elicit any proliferative response, but extracts of kidney, brain, uterus, and spleen produced proliferative responses equal to or greater than the response obtained with 50% horse serum and cholera toxin. Kidney extracts prepared from midpregnant mice, virgin mice, and virgin mice given pituitary isografts all showed comparable activities, suggesting that the concentration of stimulatory factor(s) was not influenced by the hormonal status of the donor. Normal mammary epithelial cells that had undergone a 10- to 15-fold increase in cell number over initial values during 2-3 weeks in culture were passaged to secondary gel cultures. Outgrowth similar to those seen in primary culture were seen again in secondary culture. The present system provides a method for sustaining growth in culture of primary mammary epithelial cells from normal tissues.